Design Principles of Learning Messages in E-Learning - Rama Faiz Pangestu; Herman Dwi Surjono (Jurnal Pedagogi dan Pembelajaran, 2023)
Some things still need more attention in the content or messages contained in e-learning. Therefore, good message planning or arrangement is needed concerning the principles of learning message design. This scientific study aims to analyze the application of learning message design principles in e-learning media. This study uses a qualitative descriptive approach with the type of research that is descriptive content analysis. The stages of content analysis research include formulating analysis objectives, conceptualization, and operationalization, coding sheet or instrument grids, population and sample determination, coding process, data input, and analysis. Data collection in the research was carried out using the document study method, with the research instrument in the form of coding sheets based on the definition of applying the principles of learning message design. The data analysis technique uses descriptive qualitative analysis. The results of the research analysis show that the contents of the message illustrate that in e-learning besmart, the e-learning development course has applied the principles of readiness and motivation, the principle of using the object of focus of attention, the principle of student participation, the principle of iteration, and the principle of feedback. However, it has not implemented the initial ability test as a form of readiness principle.